2016
DOI: 10.1063/1.4943002
|View full text |Cite
|
Sign up to set email alerts
|

Communication: Enhanced dissociative chemisorption of CO2 via vibrational excitation

Abstract: Quantum and classical dynamics of water dissociation on Ni(111): A test of the site-averaging model in dissociative chemisorption of polyatomic molecules

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
76
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 54 publications
(88 citation statements)
references
References 48 publications
8
76
4
Order By: Relevance
“…Such a precursor has been observed on several metal surfaces and predicted by DFT calculations, notably on Fe and Ni, although no such species has been computationally identified on Pt. Recent theoretical studies of the dissociative chemisorption of CO 2 identified the key dynamical role played by the chemisorbed CO 2 species on transition‐metal surfaces . This work shows that investigations of steps and other defects could be potentially important in finding optimal conditions for the chemical activation of CO 2 .…”
Section: Figuresupporting
confidence: 82%
See 1 more Smart Citation
“…Such a precursor has been observed on several metal surfaces and predicted by DFT calculations, notably on Fe and Ni, although no such species has been computationally identified on Pt. Recent theoretical studies of the dissociative chemisorption of CO 2 identified the key dynamical role played by the chemisorbed CO 2 species on transition‐metal surfaces . This work shows that investigations of steps and other defects could be potentially important in finding optimal conditions for the chemical activation of CO 2 .…”
Section: Figuresupporting
confidence: 82%
“…This work shows that investigations of steps and other defects could be potentially important in finding optimal conditions for the chemical activation of CO 2 . Also, the apparent excitation of the asymmetric stretching vibration in the CO 2 production as seen in our dynamics simulations suggests that this mode may be helpful in dissociative CO 2 adsorption, as already proposed …”
Section: Figuresupporting
confidence: 82%
“…The present results are in sharp contrast to the case of CO 2 dissociation, in which the CO 2 symmetric and antisymmetric stretching modes are theoretically suggested to be more important to increase the dissociation rate. 22 The importance of stretching modes in the CO 2 dissociation was implied experimentally in the study of CO 2 dynamics from CO oxidation on Pd surfaces. [23][24][25] The desorbed CO 2 has 0.12-0.16 eV in the vibrational energy of the antisymmetric mode, which is slightly larger than the vibrational energy of the CO 2 symmetric-bending mode (0.11-0.13 eV).…”
mentioning
confidence: 99%
“…Even for simplest diatomic adsorbates just accounting for the molecular DOFs (the position of the molecule's center of the mass above the surface, its bond length and angular orientation) leads already to a six-dimensional PES that needs to be computed and represented. Explicitly treating at least all these molecular DOFs has thereby been established as a complete necessity by numerous studies which have specifically outlined the dangers of a reduced dimensionality treatment and shown how (intuition-based) simplifications over the adsorbate coordinates can yield dramatically wrong results with respect to extracted dynamical properties [2,[24][25][26][27][28][29][30][31]. A proper description of the beamensemble requires on top of this extensive statistical sampling of typically several tens of thousands of impinging molecular trajectories starting from varying initial conditions.…”
Section: Gsd Within the Frozen Surface Approximationmentioning
confidence: 99%